The role of the family and higher education institutions in the entrepreneurial potential of students:What has changed in 10 years in Portugal? - Vicente, Carolina Alexandre (2019)
Dissertação de Mestrado em Psicologia do Trabalho, das Organizações e dos Recursos Humanos apresentada à Faculdade de Psicologia e de Ciências da Educação